2014
DOI: 10.1111/hdi.12198
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent hemodialysis treatment in cefepime‐induced neurotoxicity: Case report, pharmacokinetic modeling, and review of the literature

Abstract: Cefepime is a broad-spectrum cephalosporin indicated for in-hospital treatment of severe infections. Acute neurotoxicity, an increasingly recognized adverse effect of this drug in an overdose, predominantly affects patients with reduced renal function. Although dialytic approaches have been advocated to treat this condition, their role in this indication remains unclear. We report the case of an 88-year-old female patient with impaired renal function who developed life-threatening neurologic symptoms during ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…Although this Austrian group did not report significant side effects in their patients, the relatively high cefepime trough plasma concentrations which they measured were initially of concern to us because severe neurological side effects have been described with high levels of several beta-lactam antibiotics including cefepime [ 20 22 ]. Recently, Lamoth et al reported that the probability of cefepime-associated neurological toxicity (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this Austrian group did not report significant side effects in their patients, the relatively high cefepime trough plasma concentrations which they measured were initially of concern to us because severe neurological side effects have been described with high levels of several beta-lactam antibiotics including cefepime [ 20 22 ]. Recently, Lamoth et al reported that the probability of cefepime-associated neurological toxicity (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…They propose prescribing a fixed post-dialysis dose of 2 g three-times-weekly, but it should be noted that this dosage was associated with relatively high mean residual cefepime serum concentrations, e.g. 23 ± 7 mg/l [ 18 ], that may be associated to an increased risk of neurotoxicity [ 20 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hemodialysis rapidly removes cefepime from blood and CSF and hastens recovery, especially in life-threatening situations. There have been several reports of emergent hemodialysis with successful results [2,6,14,41,45,46,74,82].…”
Section: Dialysismentioning
confidence: 99%
“…normalities, some described as CIN with TW or GPD [3,15,17,22,24,43,49,[70][71][72][73][74][75][76], whereas others reported these as CIN with NCSE [4][5][6]13,14,16,18,20,21,42,45,[77][78][79][80][81][82][83][84], depending on the author's view. Some investigators proposed that encephalopathies with GPD or severe metabolic encephalopathies with continuous epileptiform EEG abnormality are not NCSE, and that a coma with continuous generalized epileptiform discharges (coma-GED) should be differentiated from NCSE proper [67,69].…”
mentioning
confidence: 99%
See 1 more Smart Citation